1997
DOI: 10.1093/oxfordjournals.aje.a009185
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass and 26-Year Risk of Mortality among Women Who Never Smoked: Findings from the Adventist Mortality Study

Abstract: The authors have examined the relation between the Quetelet body mass index (BMI) and 26-year risk of all-cause mortality in a population of 12,576 non-Hispanic while, Seventh-day Adventist women (ages 30-74 years) who never smoked. Mortality risk for each BMI quintile (I, < 21.3 kg/m2; II, 21.3-22.9 kg/m2; III, 23.0-24.8 kg/m2; IV, 24.9-27.4 kg/m2; and V, > 27.4 kg/m2) was determined from a proportional hazard regression with adjustment for age and other covariables. In this population, the overall BMI-mortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
52
1
3

Year Published

1998
1998
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 36 publications
2
52
1
3
Order By: Relevance
“…However, six 48,49,53,54,59,66 out of seven showed lower mortality in subjects with lower BMI, or at least a U-shaped relation between BMI and mortality. It is important to note that none of these studies were able to distinguish between intentional and unintentional weight loss.…”
Section: Obesity and Aging M Zamboni Et Almentioning
confidence: 87%
See 4 more Smart Citations
“…However, six 48,49,53,54,59,66 out of seven showed lower mortality in subjects with lower BMI, or at least a U-shaped relation between BMI and mortality. It is important to note that none of these studies were able to distinguish between intentional and unintentional weight loss.…”
Section: Obesity and Aging M Zamboni Et Almentioning
confidence: 87%
“…However, when only people who never smoked were studied, two studies out of three 48,60,63 observed linear relation between BMI and mortality among older subjects, suggesting that increased mortality associated with the lowest weights were a function of cigarette smoking, and that, among never-smokers, very low weights were associated with the greatest longevity.…”
Section: Obesity and Aging M Zamboni Et Almentioning
confidence: 99%
See 3 more Smart Citations